If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5 + 7p) = 33 + -5p (5 * -3 + 7p * -3) = 33 + -5p (-15 + -21p) = 33 + -5p Solving -15 + -21p = 33 + -5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5p' to each side of the equation. -15 + -21p + 5p = 33 + -5p + 5p Combine like terms: -21p + 5p = -16p -15 + -16p = 33 + -5p + 5p Combine like terms: -5p + 5p = 0 -15 + -16p = 33 + 0 -15 + -16p = 33 Add '15' to each side of the equation. -15 + 15 + -16p = 33 + 15 Combine like terms: -15 + 15 = 0 0 + -16p = 33 + 15 -16p = 33 + 15 Combine like terms: 33 + 15 = 48 -16p = 48 Divide each side by '-16'. p = -3 Simplifying p = -3
| -2(x+7)=4x-7 | | -4=13.7 | | 15-3x=12-5x | | 4w(w-6)-2w^2=2w^2+8w-4 | | 2+3n=0.8n+18 | | 14-x=3x-2 | | x^3+5x^2+16x+80=0 | | 4/28=x/147 | | -7(x-6)-8=-5x+40 | | 5W+W=36 | | h=9(8m-9r) | | 6(-6-5)-6=0 | | ln(x+11)+ln(x-3)=2lnx | | 0=a^2-18a+72 | | 4x+6=-7x-7 | | -15t^2+60t=0 | | 5t+6-8t=30 | | 24t^2+19t+2=0 | | .25p+7=3 | | (2x^2-5x-3)=0 | | 2q+30=6-4q | | 50x=20x+10 | | 3x+5+6x=113 | | 50x=20x+30 | | x-2+25=66-2+3x | | 6p-2(p+6)=20 | | 0.5d-8=3 | | -4b+40=-4(2b-5) | | -10-0.5x=-27.5 | | x-2+25=66-2+x | | 5d+6=3d+16 | | 3x^2+18x-10=0 |